2016
DOI: 10.17509/ijost.v1i1.2211
|View full text |Cite
|
Sign up to set email alerts
|

A novel In-situ Enzymatic Cleaning Method for Reducing Membrane Fouling in Membrane Bioreactors (MBRs)

Abstract: A novel in-situ enzymatic cleaning method was developed for fouling control in membrane bioreactors (MBRs). It is achieved by bringing the required enzymes near the membrane surface by pulling the enzymes to a magnetic membrane (MM) surface by means of magnetic forces, exactly where the cleaning is required. To achieve this, the enzyme was coupled to a magnetic nanoparticle (MNP) and the membrane it self was loaded with MNP. The magnetic activity was turned by means of an external permanent magnet. The effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A selectively permeable membrane allows passage of water, but largely rejects solute molecules and ions. (Bilad et al, 2016) FO has emerges as a promising alternative for various applications because of its several key advantages. FO membrane fouling propensity is considered low and more reversible (Achilli et al, 2009;S.…”
Section: Introductionmentioning
confidence: 99%
“…A selectively permeable membrane allows passage of water, but largely rejects solute molecules and ions. (Bilad et al, 2016) FO has emerges as a promising alternative for various applications because of its several key advantages. FO membrane fouling propensity is considered low and more reversible (Achilli et al, 2009;S.…”
Section: Introductionmentioning
confidence: 99%
“…Another promising method for the regeneration of IEMs after their contact with liquid media of the food industry is the use of enzymatic agents specific to certain types of substances. They performed well in the case of cleaning of ultrafiltration membranes fouled by proteins [196] or in the case of reducing membrane fouling in bioreactors [197]. Bdiri et al [198] first tested protease and β-glucanase, as well as polyphenol oxidase, which enter the specific interactions with proteins, polysaccharides, and phenolic compounds, respectively, as well as mixtures of these enzymes.…”
Section: Non-destructive Methods Of Membrane Fouling Controlmentioning
confidence: 99%
“…The second one is a periodic cleaning of membranes using acids, alkalis, perchlorates, and other oxidizing agents [ 90 ] or enzymes [ 9 , 114 , 247 , 248 , 249 ]. Xue et al [ 90 ] clearly demonstrated the effectiveness of such treatment ( Figure 25 ).…”
Section: Innovations In Nutrient Recovery Processes With Ion-exchange...mentioning
confidence: 99%